(untitled) (Encuentros, 2022)
This article seeks to determine whether there are inconsistencies in the budgetary operation of the resources belonging to the school feeding program (PAE) by comparing two government information sources. For this purpose, a descriptive statistical analysis was performed on 380 reports from 2018, available on the Colombian Ministry of National Education (MEN) website, which shows the operation carried out by 95 certified territorial entities (ETC) in the PAE. In addition, the total and unit costs reported in the typical exchange before the Consolidator of Finance and Public Information (CHIP) and the resources allocated to the PAE from the transfers made by the MEN and the General System of Participations (SGP) were compared. The findings show that, when comparing the unit costs, there are differences in the information reported, determining that the control processes of the MEN are imperfect when controlling the resources allocated to the nutrition of schoolchildren.